Theoretical Foundations for Calculating the Erosion of Soil Dams during Overflow of Water over the Ridge - V. V. Ivashechkin; P. M. Bohaslauchyk; V. V. Veremenyuk; O. V. Nemeravets (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Large-scale hydraulic engineering construction associated with the erection and operation of large dams and reservoirs has an impact on the ecosystem and physical and geographical characteristics of the construction area. In addition, during the passage of catastrophic floods and high waters, the danger of a hydrodynamic accident increases, i. e. overflow of reservoirs, overflow of masses over the ridge of an earthen dam and its destruction, accompanied by the formation of a closure channel and the outflow of an unsteady water flow through it into the lower reaches in the form of a breakthrough wave. The process of erosion of an underground dam due to the overflow of water over the ridge can be divided into two stages. During the first one, the lower slope is eroded, along which the water moves as if by a rapid current. The profile of the dam, initially trapezoidal, by the end of the erosion takes a shape close to triangular, and the ridge mark on the side of the upper slope remains constant. The second stage is characterized by an intensive reduction of the ridge; the dam quickly takes the form of a practical profile spillway, which persists until the end of erosion. At the same time, there is an intensive expansion of the closure channel. As the analysis showed, the existing mathematical models used to calculate the dynamics of the erosion of the dam, especially its first stage before the expansion of the closure channel, are not perfect. The article presents a refined methodology developed by the authors for modeling the process of erosion of ground dams during water overflow over the ridge. The calculations made in accordance with this methodology make it possible to construct a flow hydrograph in the location of the eroded dam. The methodology can be used in the development of project documentation at the first stage of dam design, as well as in determining the forecast quantitative and qualitative characteristics of the water regime of reservoirs.